The Contribution of Area MT to Visual Motion Perception Depends on Training - Liu, Liu D.; Pack, Christopher C. (Neuron (Cambridge, Mass.), 2017)
Perceptual decisions require the transformation of raw sensory inputs into cortical representations suitable for stimulus discrimination. One of the best-known examples of this transformation involves the middle temporal area (MT) of the primate visual cortex. Area MT provides a robust representation of stimulus motion, and previous work has shown that it contributes causally to performance on motion discrimination tasks. Here we report that the strength of this contribution can be highly plastic: depending on the recent training history, pharmacological inactivation of MT can severely impair motion discrimination, or it can have little detectable influence. Further analysis of neural and behavioral data suggests that training moves the readout of motion information between MT and lower-level cortical areas. These results show that the contribution of individual brain regions to conscious perception can shift flexibly depending on sensory experience. •Little effect of MT inactivation on motion percepts of subjects trained on gratings•After training with dots, MT inactivation impairs perception of dots and gratings•Choice probability is more correlated with neural sensitivity after dots training•Spatial integration is greater when subjects are trained with dots Liu and Pack show that visual motion perception can rely on different brain areas, depending on training. After training with random dot stimuli, perceptual decisions rely on MT, but with training on grating stimuli, decisions are based on lower-level cortical areas.